Another time, another place - Taylor, Jodi (Taylor, Jodi. Chronicles of St. Mary's, 2021)
"It's long been known that if a thing can go wrong, it will. With knobs on, usually. Disasters start to pile up. A new colleague with no respect for the past and a great deal to prove. Historians lost in time. And - worst of all - Rosie Lee on her very first jump. Then there's the small matter of Max's dishonourable discharge. From Tudor England to the Tower of Babel - it's all going horribly wrong. Jobless and homeless, Max receives an offer she can't refuse. Another time, another place. A refuge, perhaps.She's got that wrong, too."--Publisher.